Mapping: a speculative and creative design tool - Zakariya, Khalilah; Mansor, Mazlina; Harun, Nor Zalina (Chitkara University, Punjab, 2015)
Mapping is a technique used to record and represent information graphically. In the studios made for architecture and landscape architecture, mapping is usually conducted at the Inventory-making and Analysis stage. Data from the site is gathered and documented for further investigation. However, mapping can also become a creative tool to ‘reveal’ certain things or invisible processes. It can encourage the designers to speculate the site and the design from different perspectives and at multiple scales. This paper discusses some mapping projects that have been explored by the authors through their research projects. The aim of this paper is to recommend mapping as a creative and speculative design tool that can make data more engaging to design thinking.